(untitled) (Comprehensive Journal of Science, 2025)
This current study aims to examine the obstacles to change management in higher education institutions and ways to overcome them amid the rapid transformations occurring in university education. It also reviews the components of change management, which include clarity of vision and goals, support from university leadership, active participation of human resources, availability of material and technological resources, and the development of an organizational culture that supports change. The study addresses the main obstacles to change management, including human-related obstacles such as resistance to change and lack of awareness of its importance, technological obstacles related to weak infrastructure and limited training, administrative obstacles such as centralization and organizational rigidity, and technical obstacles characterized by lack of expertise and weak information systems. The study recommends adopting effective strategies for change management that contribute to improving institutional performance and achieving quality in higher education, raising human resource awareness, fostering an organizational culture that encourages change, developing technological infrastructure, enhancing information system efficiency, promoting administrative flexibility, and improving performance- and change-related incentive systems.